2022
DOI: 10.1002/smll.202201088
|View full text |Cite
|
Sign up to set email alerts
|

New Mechanism for Long Photo‐Induced Enhanced Raman Spectroscopy in Au Nanoparticles Embedded in TiO2

Abstract: Cathodoluminescence: The CL analysis was performed with a Horiba HCLUE coupled with a scanning electron microscope ZEISS EVO MA15. The CL analysis was performed at an acceleration voltage of 10 kV. The measurement was done before UV irradiation or immediately after.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 49 publications
3
14
0
Order By: Relevance
“…Panels a and b of Figure depict the SERS spectra of rhodamine 6G (R6G) molecules from the samples with and without an Al 2 O 3 coating during the band alignment. As shown in Figure a, significant SERS enhancement was observed for the UV-preirradiated sample (0 h) compared with the unirradiated one (pristine), and the SERS intensity decreased with time during the healing of the oxygen vacancy defects until a balance was reached after 72 h. The phenomenon is consistent with the observations in previous reports, but it was considered that the charge transfers between the heterojunction and molecules were responsible for the Raman enhancement. ,, This viewpoint is not well supported by our experimental results in Figure b, where a similar tendency was still observed when the charge transfers between the heterojunction and molecules were blocked by a 2 nm thick Al 2 O 3 layer. The results suggest the charge transfer between the heterojunction and molecules is not the major contributor to the observed SERS enhancement.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Panels a and b of Figure depict the SERS spectra of rhodamine 6G (R6G) molecules from the samples with and without an Al 2 O 3 coating during the band alignment. As shown in Figure a, significant SERS enhancement was observed for the UV-preirradiated sample (0 h) compared with the unirradiated one (pristine), and the SERS intensity decreased with time during the healing of the oxygen vacancy defects until a balance was reached after 72 h. The phenomenon is consistent with the observations in previous reports, but it was considered that the charge transfers between the heterojunction and molecules were responsible for the Raman enhancement. ,, This viewpoint is not well supported by our experimental results in Figure b, where a similar tendency was still observed when the charge transfers between the heterojunction and molecules were blocked by a 2 nm thick Al 2 O 3 layer. The results suggest the charge transfer between the heterojunction and molecules is not the major contributor to the observed SERS enhancement.…”
supporting
confidence: 79%
“…The defect level is typically located at ∼0.7 eV below the TiO 2 conduction band edge (as illustrated in Figure c), which grants additional donor states within the bandgap, and leads to the ground-state charge transfer from TiO 2 to Ag. This band alignment decreases the number of charges in TiO 2 , leading to an increase in the dielectric constant of the surrounding medium . On the basis of the Drude model, the resonant frequency ω LSPR of a plasmonic metal can be expressed as where N is the free carrier density, ε 0 is the permittivity of free space, ε m is the dielectric constant of the surrounding medium, and m e is the effective mass of the free carrier (electron in this case).…”
mentioning
confidence: 99%
“…37 This is further confirmed by in situ Raman characterization with different excitation wavelengths that can penetrate different depths. As shown in Figure 1C,D, the characteristic peak of the anatase at 396, 514, and 638 cm À1 could be observed in Pd/TiO 2 -P. 34,38 With the treatment temperature increasing to 700 C, it is found that the peaks shift slightly toward lower position and become broadening. This could be due to the slight transformation of anatase to rutile under high-temperature reduction, but without the obvious characteristic peaks of rutile at 448 and 611 cm À1 .…”
Section: Catalytic Testsmentioning
confidence: 85%
“…241 Especially, the enhancement ability of the composite substrates of plasmonic metals and photo-activated semiconductors can be further improved by an emerging technique called photo-induced enhanced Raman scattering (PIERS). 196,[242][243][244][245] In PIERS, the substrates need to be irradiated with a second light before or during the Raman testing in order to foster the CT processes between semiconductors and metals, enabling strong Raman enhancement and improved sensitivity beyond the normal SERS effect. 196,242 In 2016, Parkin's group reported the PIERS effect on Au/ AgNP-TiO 2 substrates, which showed stronger enhancement with an order of magnitude to target molecules including dyes, explosives, and biomolecules over SERS (e.g., rhodamine 6G shown in Fig.…”
Section: Nanocomposites Consisted Of Metal and Sers-active Nonmetal N...mentioning
confidence: 99%